High-durability flow battery diaphragm and preparation method thereof

By adding thermosetting epoxy sulfonic acid resin and thermosetting curing agent to the high-equivalent perfluorosulfonic acid resin dispersion of the liquid flow battery separator, the problems of reducing efficiency and shortening of vanadium ion penetration are solved, and high durability and good mechanical properties are achieved.

CN119812379APending Publication Date: 2025-04-11SHENZHEN GENERAL HYDROGEN ENERGY TECH CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411965262.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional flow battery separators have problems of reduced efficiency and shortened lifetime in vanadium ion penetration, and the prior art is difficult to maintain proton conductivity and tensile properties while increasing the film thickness.

Method used

A thermosetting epoxy sulfonic acid resin and a thermosetting curing agent were added to the high-equivalent perfluorosulfonic acid resin dispersion, and a high-durability flow battery separator was prepared by step-by-step heating and curing, and a high-equivalent resin was added to the top and bottom layers. A low-equivalent resin dispersion was used in the middle layer to improve the proton conduction efficiency.

Benefits of technology

The vanadium resistance rate of the flow battery separator is significantly reduced, the mechanical properties are improved, and the battery performance remains basically unchanged after 5,000 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812379A_ABST
    Figure CN119812379A_ABST
Patent Text Reader

Abstract

The invention discloses a high-durability flow battery diaphragm and a preparation method thereof, which are characterized in that thermosetting epoxy sulfonic acid resin and a thermosetting curing agent are added into high-equivalent perfluorinated sulfonic acid resin dispersion liquid with the resin equivalent of 900-1300g / mol, and the mixture is cured and molded. The thermosetting epoxy sulfonic acid resin is added into the high-equivalent resin dispersion liquid, so that the vanadium resistance rate of the flow battery diaphragm is remarkably reduced, and the mechanical property is improved. The invention also provides a battery diaphragm taking high and low equivalent resin dispersion liquid as raw materials, high equivalent resin is added to the top layer and the bottom layer, thermosetting epoxy sulfonic acid resin is added to reduce the vanadium resistance rate of the flow battery diaphragm and improve the mechanical property, and the low equivalent resin dispersion liquid is used in the middle layer to improve the proton conduction efficiency of the flow battery diaphragm. The flow battery diaphragm is prepared through a low-temperature pre-drying and high-temperature one-time forming process. The performance of the prepared flow battery is basically kept unchanged after 5000 cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a high-durability liquid flow battery separator and a preparation method thereof. Background Art

[0002] Traditional flow battery separators are mainly prepared and synthesized with high equivalent perfluorosulfonic acid resin. In flow batteries, due to the cross diffusion of vanadium, the battery efficiency will be reduced and the life will be shortened. In order to reduce the penetration of vanadium ions, common technical methods are:

[0003] Adding vanadium inhibitors: By adding certain vanadium inhibitors to the proton exchange membrane, the membrane's selectivity and barrier properties for vanadium can be enhanced, reducing the penetration of vanadium ions.

[0004] Increasing membrane thickness: Although increasing the membrane thickness may slightly improve its barrier capacity for vanadium ions, it may also result in decreased proton conductivity and decreased membrane stretchability.

[0005] Therefore, a trade-off between the two is usually required when designing film thickness. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.

[0007] As one aspect of the present invention, the present invention provides a method for preparing a high-durability liquid flow battery separator: adding a thermosetting epoxysulfonic acid resin and a thermosetting curing agent to a high-equivalent perfluorosulfonic acid resin dispersion with a resin equivalent of 900 to 1300 g / mol, and curing and forming.

[0008] As a preferred embodiment of the method for preparing the high-durability liquid flow battery separator of the present invention: the amount of the thermosetting epoxysulfonic acid resin added to the high equivalent weight perfluorosulfonic acid resin dispersion is 1 to 15 wt %.

[0009] As a preferred embodiment of the method for preparing the high-durability liquid flow battery separator described in the present invention: the curing molding includes curing molding in a step-by-step heating method, and the heating methods are: 50-60°C, 25-40min; 90-110°C, 20-30min; 160-190°C, 10-20min.

[0010] As a preferred solution of the method for preparing the high-durability liquid flow battery separator of the present invention: the addition amount of perfluorosulfonic acid in the high equivalent perfluorosulfonic acid resin dispersion is 15-40%.

[0011] As a preferred embodiment of the method for preparing the high-durability liquid flow battery separator of the present invention: the solvent of the high-equivalent perfluorosulfonic acid resin dispersion includes one or more of dimethyl sulfone, N,N-dimethylformamide, and propylene glycol methyl ether acetate.

[0012] As a preferred embodiment of the method for preparing the high-durability liquid flow battery separator of the present invention: the thermosetting curing agent includes one or more of triethylamine, triethanolamine, and tris(dimethylaminomethyl)phenol; the addition amount of the thermosetting curing agent is 0.05-0.5wt%.

[0013] The present invention also provides a method for preparing a high-durability liquid flow battery diaphragm, comprising the following steps:

[0014] Step 1: adding a thermosetting epoxysulfonic acid resin and a thermosetting curing agent to a high equivalent weight perfluorosulfonic acid resin dispersion having a resin equivalent weight of 900 to 1300 g / mol to obtain a dispersion 1, applying a film by scraping, laying a layer of ePTFE reinforcement layer, and heating at 50 to 60° C. to obtain a film 1;

[0015] Step 2: coating a low equivalent weight perfluorosulfonic acid resin dispersion on the ePTFE reinforcement layer of the film 1 and adding the ePTFE reinforcement layer, and heating at 50-60° C. to obtain an intermediate layer; wherein the resin equivalent of the low equivalent weight perfluorosulfonic acid resin is 760-850 g / mol;

[0016] Step 3: coating the dispersion 1 on the membrane obtained in step 2, and curing and molding the membrane to obtain the high-durability liquid flow battery separator.

[0017] As a preferred scheme for the preparation method of the high-durability liquid flow battery membrane described in the present invention: in step 2, the amount of perfluorosulfonic acid resin added to the low equivalent perfluorosulfonic acid resin dispersion is 10 to 30 wt%; the intermediate layer is provided with several layers, and in the intermediate layer, the low equivalent perfluorosulfonic acid resin layer and the ePTFE reinforced layer are spaced apart.

[0018] As a preferred solution of the method for preparing the high-durability liquid flow battery separator of the present invention: 0.1-1 wt% cerium nitrate and 0.1-1 wt% Triton X-100 are further added to the low equivalent perfluorosulfonic acid resin dispersion.

[0019] Beneficial effects of the present invention: The present invention adds a thermosetting epoxy sulfonic acid resin to a high equivalent weight resin dispersion, which significantly reduces the vanadium resistance rate of the liquid flow battery diaphragm and improves the mechanical properties. The present invention also provides a battery diaphragm using high and low equivalent weight resin dispersions as raw materials, adding a high equivalent resin to the top and bottom layers, and adding a thermosetting epoxy sulfonic acid resin to reduce the vanadium resistance rate of the liquid flow battery diaphragm and improve the mechanical properties, and using a low equivalent weight resin dispersion in the middle layer to increase the proton conduction efficiency of the liquid flow battery diaphragm. The liquid flow battery diaphragm is prepared by a low-temperature pre-baking and high-temperature one-time molding process. After 5,000 cycles, the performance of the prepared liquid flow battery remains basically unchanged. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:

[0021] Figure 1 Energy efficiency of the flow battery membranes obtained in various examples and the commercial Nafion 115 membrane at different current densities.

[0022] Figure 2 The coulombic efficiency of the flow battery membrane obtained in each embodiment at different current densities.

[0023] Figure 3 Proton conductivity of different flow battery membranes in water at different temperatures.

[0024] Figure 4 160mA / cm at 5000 cycles 2 Example 4 Performance attenuation test of liquid flow battery membrane.

[0025] Figure 5 This is the SEM image of the flow battery membrane F-4 of Example 4.

[0026] Figure 6 This is the SEM image of the liquid flow battery membrane F-6 of Example 6.

[0027] Figure 7 It is a schematic diagram of the molecular planar structure in the liquid flow battery diaphragm of the present invention.

[0028] Figure 8 This is a performance attenuation test of the flow battery membrane in Example 1. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0030] Experimental materials: DMSO (dimethyl sulfone), DMF (N, N-dimethylformamide), PGMEA (propylene glycol methyl ether acetate), PFSA (perfluorosulfonic acid resin), Triton X-100, ePTFE (expanded polytetrafluoroethylene, pore size 0.2~0.3μm, porosity 70~90%).

[0031] Embodiment 1:

[0032] In parts by weight, 300 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250 g / mol, 28 wt% PFSA, the rest being high boiling point solvent DMF), 15 parts of thermosetting epoxysulfonic acid resin A1, 0.5 parts of triethylamine, and 25 parts of DMF were mixed evenly, then coated into a film, and then cured by stepwise heating at 50°C for 25 min, 100°C for 30 min, and 180°C for 15 min to obtain a liquid flow battery separator F-1 with a single layer thickness of 30 μm.

[0033] Embodiment 2:

[0034] In parts by weight, 300 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250 g / mol, 33 wt% PFSA, the rest being high boiling point solvent DMF), 15 parts of thermosetting epoxysulfonic acid resin A1, 0.5 parts of triethylamine, and 25 parts of DMF were mixed evenly, then coated into a film, and cured by stepwise heating at 50°C for 25 min, 100°C for 30 min, and 180°C for 15 min to obtain a liquid flow battery separator F-2 with a single layer thickness of 50 μm.

[0035] Embodiment 3:

[0036] In parts by weight, 300 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250 g / mol, 33 wt% PFSA, the rest being high boiling point solvent DMF), 15 parts of thermosetting epoxysulfonic acid resin A1, 0.5 parts of triethylamine, and 25 parts of DMF were mixed evenly, then coated into a film, and cured by stepwise heating at 50°C for 25 min, 100°C for 30 min, and 180°C for 15 min to obtain a liquid flow battery separator F-3 with a single layer thickness of 100 μm.

[0037] Embodiment 4:

[0038] 1. In parts by weight, 200 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250 g / mol, 25wt% PFSA, 75wt% solvent DMF), 15 parts of thermosetting epoxysulfonic acid resin A1, 0.5 parts of triethylamine, and 25 parts of DMF were mixed evenly to obtain dispersion 1, which was then coated to form a film, and a layer of ePTFE reinforcement layer with a thickness of about 10 μm was laid flat, and a film 1 was obtained after being treated at 50° C. for 40 min. The thickness of the film 1 was about 25 μm;

[0039] 2. 100 parts of low equivalent weight perfluorosulfonic acid resin dispersion (equivalent weight 790 g / mol, 20 wt% PFSA, 80 wt% propanol solution), 20 parts of n-propanol, 5 parts of DMF, 0.5 parts of cerium nitrate, and 0.5 parts of Triton X-100 are mixed evenly and coated on the surface of the ePTFE reinforcement layer of film 1, and then a layer of ePTFE reinforcement layer with a thickness of about 4 to 5 μm is laid after coating, and film 2 is obtained after 50°C for 40 minutes. The thickness of the film obtained after preparation in steps 1 and 2 is about 30 μm;

[0040] 3. The dispersion 1 is coated on the surface of the ePTFE reinforced layer of the membrane 2 obtained in step 2, and cured by stepwise heating at 50°C for 25 min, 100°C for 30 min, and 180°C for 15 min to obtain a liquid flow battery separator F-4 with a total thickness of 50 μm.

[0041] Embodiment 5:

[0042] 1. In terms of weight, 200 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250 g / mol, 25 wt% PFSA, 75 wt% solvent DMF), 15 parts of thermosetting epoxysulfonic acid resin A1, 0.5 parts of triethylamine, and 25 parts of DMF were mixed evenly to obtain dispersion 1, which was then coated to form a film, and a layer of ePTFE reinforcement layer with a thickness of about 10 μm was spread, and the film 1 was treated at 50° C. for 40 min to obtain a film with a thickness of about 25 μm;

[0043] 2. 100 parts of low equivalent weight perfluorosulfonic acid resin dispersion (equivalent weight 790 g / mol, 20 wt% PFSA, 80 wt% propanol solution), 20 parts of n-propanol, 5 parts of DMF, 0.5 parts of cerium nitrate, and 0.5 parts of Triton X-100 were mixed evenly and coated on the surface of the ePTFE reinforcement layer of film 1, and then a layer of ePTFE reinforcement layer with a thickness of about 4 to 5 μm was laid after coating, and film 2 was obtained after 50°C for 40 minutes. The thickness of the film obtained after steps 1 and 2 is 75 μm;

[0044] 3. The dispersion 1 is coated on the surface of the ePTFE reinforced layer of the membrane 2 obtained in step 2, and cured by stepwise heating at 50°C for 25 min, 100°C for 30 min, and 180°C for 15 min to obtain a liquid flow battery separator F-5 with a total thickness of 100 μm.

[0045] Embodiment 6:

[0046] 1. In parts by weight, 200 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250 g / mol, 25wt% PFSA, 75wt% solvent DMF), 15 parts of thermosetting epoxysulfonic acid resin A1, 0.5 parts of triethylamine, and 25 parts of DMF were mixed evenly to obtain dispersion 1, which was then coated to form a film, and a layer of ePTFE reinforcement layer with a thickness of about 10 μm was spread, and a film 1 was obtained after being treated at 50° C. for 40 min. The thickness of the film 1 was about 40 μm;

[0047] 2. 100 parts of low equivalent weight perfluorosulfonic acid resin dispersion (equivalent weight 790 g / mol, 20 wt% PFSA, 80 wt% propanol solution), 20 parts of n-propanol, 5 parts of DMF, 0.5 parts of cerium nitrate, and 0.5 parts of Triton X-100 were mixed evenly and coated on the surface of the ePTFE reinforcement layer of film 1, and then a layer of ePTFE reinforcement layer with a thickness of about 4 to 5 μm was laid after coating, and film 2 was obtained after 50°C for 40 minutes. The thickness of the film obtained after steps 1 and 2 is 50 μm;

[0048] 3. 100 parts of low equivalent weight perfluorosulfonic acid resin dispersion (equivalent weight 790 g / mol, 20 wt% PFSA, 80 wt% propanol solution), 20 parts of n-propanol, 5 parts of DMF, 0.5 parts of cerium nitrate, and 0.5 parts of Triton X-100 were mixed evenly and coated on the surface of the ePTFE reinforcement layer of film 2, and then a layer of ePTFE reinforcement layer with a thickness of about 4 to 5 μm was laid after coating, and film 3 was obtained after 50°C for 40 minutes; the thickness of the film obtained after steps 1 to 3 was 60 μm;

[0049] 4. The dispersion 1 was coated on the surface of the ePTFE reinforcement layer of the membrane 3, and cured by stepwise heating at 50°C for 25 min, 100°C for 30 min, and 180°C for 15 min to obtain a liquid flow battery separator F-6 with a total thickness of 100 μm.

[0050] The test results of thickness, tensile properties, and vanadium ion permeability of the commercial Nafion 115 membrane and the flow battery membranes prepared in various embodiments are shown in Table 1.

[0051] Table 1

[0052]

[0053] As can be seen from Table 1, compared with the commercial Nafion 115 membrane, the F-1 membrane in Example 1 to which the thermosetting epoxysulfonic acid resin A1 is added significantly reduces the vanadium ion permeability and greatly improves the tensile properties at a significantly thinner thickness (30 μm). As the membrane thickness increases, the tensile properties of the membrane decrease significantly, and the vanadium barrier properties improve; the tensile properties of Example 3 (F-3) are significantly reduced, while the vanadium barrier properties are significantly improved as the membrane thickness increases. Examples 4 to 6 add an ePTFE reinforcement layer and a low equivalent weight PFSA resin layer. The addition of the ePTFE reinforcement layer can improve the tensile properties of the membrane, and improve its tensile properties when the membrane thickness is large, but the proton conduction efficiency of the membrane will be significantly reduced due to the addition of the ePTFE reinforcement layer. In order to solve the problem that the proton conduction efficiency of the membrane is significantly reduced with the addition of the ePTFE reinforcement layer, the present invention adds a low equivalent PFSA resin layer while adding the ePTFE reinforcement layer (Examples 4-6). It is found that the low equivalent PFSA resin diffuses into the ePTFE reinforcement layer and can improve the proton conduction efficiency of the finally prepared flow battery diaphragm, so that the proton conduction efficiency of the diaphragm will not be significantly reduced due to the addition of the ePTFE reinforcement layer (see Figure 3 ).

[0054] Figure 1 The energy efficiency of the flow battery membrane obtained in each example at different current densities. Figure 2 The coulombic efficiency of the flow battery membrane obtained in each embodiment at different current densities. Figure 3 Proton conductivity of different flow battery membranes in water at different temperatures. Figure 4 160mA / cm at 5000 cycles 2 Example 4 Performance attenuation test of liquid flow battery membrane. Figure 5 This is the SEM image of the flow battery membrane F-4 of Example 4. Figure 6 This is the SEM image of the liquid flow battery membrane F-6 of Example 6. Figure 7 It is a schematic diagram of the molecular planar structure in the liquid flow battery diaphragm of the present invention. Figure 8 This is a performance attenuation test of the flow battery membrane in Example 1.

[0055] Depend on Figure 1 It can be seen that the energy efficiency of conventional Nafion 115 membrane decays rapidly under different current densities. In the examples, F-1, F-2, and F-3 are all homogeneous membranes. The addition of thermosetting epoxysulfonic acid resin A1 not only facilitates proton conduction but also improves the vanadium barrier effect and significantly improves the mechanical properties of the membrane. In the examples, F-4, F-5, and F-6 use a lower equivalent PFSA resin as the middle layer. As the thickness increases, the energy efficiency decreases at 200 mA / cm 2 Maintain high energy efficiency under current.

[0056] Figure 2 The results show that the film has high coulombic efficiency at low thickness, and the coulombic efficiency remains high as the thickness increases. In particular, after adding low equivalent resin in Examples 2-6, the coulombic efficiency and energy efficiency remain good as the thickness increases. Figure 3 It can be seen that after adding the thermosetting epoxysulfonic acid resin A1, the proton conductivity of the F-1 membrane in Example 1 is relatively high, and the F-3 obtained after the thickness increases to 100 μm shows a certain downward trend. This is because the thickness increases the time of proton transmission, accompanied by an increase in internal resistance; and on the basis of Example 1, the proton conductivity after adding a low equivalent resin layer is higher than that of conventional Nafion 115. The present invention uses industrial resin (the price is about 1 / 10 of the price of Nafion), but the performance is higher than Nafion 115, which is more obvious at higher temperatures. On the other hand, with the increase in the number of layers, the proton conductivity does not decrease significantly due to the increase in thickness and the addition of the ePTFE reinforcement layer.

[0057] The difference from the traditional pure PFSA is that after the thermosetting epoxy sulfonic acid resin A1 forms a stable structure inside, a small amount of ion channels are sacrificed, and the thermosetting epoxy sulfonic acid resin A1 is used to self-crosslink at high temperature to fix the PFSA in the corresponding area. On the one hand, it is beneficial to reduce the penetration of vanadium ions, and on the other hand, it can also reduce the attack of free radicals, further extend the service life of the membrane, and improve the mechanical properties of the membrane.

[0058] The preparation method of thermosetting epoxy sulfonic acid resin A1 is prepared by referring to the literature "Preparation and Mechanical Properties of Sodium p-aminobenzenesulfonate Modified Waterborne Epoxy Resin", and the synthesis route is as follows:

[0059]

[0060] Preparation method: According to the molar ratio of 1:1 of phenolic epoxy resin F51 and sodium p-aminobenzenesulfonate, epoxy sodium sulfonate resin is synthesized at 100-140°C, and then acidified with dilute sulfuric acid to obtain thermosetting epoxy sulfonic acid resin A1. The obtained resin A1 can be dissolved in both organic solvents and water.

[0061] Comparative Example 1:

[0062] In terms of weight, 300 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250 g / mol, 28 wt% PFSA, the rest being high boiling point solvent DMF) and 25 parts of DMF were mixed evenly, then coated into a film, and then cured by stepwise heating at 50°C for 25 min, 100°C for 30 min, and 180°C for 15 min to obtain a single-layer flow battery separator with a thickness of 50 μm.

[0063] Test results: tensile properties (Mpa): 20~22Mpa;

[0064] Vanadium ion permeability (10 -7 cm 2 ·min -1 ):21.74.

[0065] The membranes prepared only with high equivalent weight perfluorosulfonic acid resin have poor mechanical properties and vanadium barrier properties, making them difficult to apply industrially.

[0066] Comparative Example 2:

[0067] 1. In terms of weight, 200 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250 g / mol, 25 wt% PFSA, 75 wt% solvent DMF) and 25 parts of DMF were mixed evenly to obtain dispersion 1, which was then coated to form a film, and a layer of ePTFE reinforcement layer with a thickness of about 10 μm was spread. The film 1 was treated at 50° C. for 40 min to obtain a film with a thickness of about 25 μm;

[0068] 2. 200 parts of perfluorosulfonic acid resin dispersion (equivalent weight 1250g / mol, 25wt% PFSA, 75wt% solvent DMF), 20 parts of n-propanol, 5 parts of DMF, 0.5 parts of cerium nitrate, and 0.5 parts of Triton X-100 were mixed evenly and coated on the surface of the ePTFE reinforcement layer of film 1, and then a layer of ePTFE reinforcement layer with a thickness of about 4 to 5μm was laid after coating, and film 2 was obtained after 50℃ for 40min. The thickness of the film obtained after steps 1 and 2 is 75μm;

[0069] 3. The dispersion 1 is coated on the surface of the ePTFE reinforced layer of the membrane 2 obtained in step 2, and cured by stepwise heating at 50°C for 25 min, 100°C for 30 min, and 180°C for 15 min to obtain a liquid flow battery diaphragm with a total thickness of 100 μm.

[0070] Proton conductivity test (80℃) result: 48mS / cm;

[0071] Test results: Tensile properties (Mpa): 16~18Mpa.

[0072] When only high equivalent weight perfluorosulfonic acid resin is added, the proton conductivity is low when the membrane thickness is high and an ePTFE reinforcement layer is added.

[0073] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a high-durability flow battery diaphragm, characterized in that: Thermosetting epoxysulfonic acid resin and thermosetting curing agent are added to a high-equivalent perfluorosulfonic acid resin dispersion with a resin equivalent of 900 to 1300 g / mol, and then cured and formed.

2. The method for preparing a high-durability liquid flow battery separator according to claim 1, characterized in that: The amount of the thermosetting epoxy sulfonic acid resin added to the high equivalent weight perfluorosulfonic acid resin dispersion is 1 to 15 wt %.

3. The method for preparing a high-durability liquid flow battery separator according to claim 1 or 2, characterized in that: The curing molding includes curing molding in a step-by-step heating method, and the heating methods are: 50-60°C, 25-40min; 90-110°C, 20-30min; 160-190°C, 10-20min.

4. The method for preparing a high-durability liquid flow battery separator according to claim 1 or 2, characterized in that: In the high equivalent weight perfluorosulfonic acid resin dispersion, the added amount of perfluorosulfonic acid is 15N40%.

5. The method for preparing a high-durability liquid flow battery membrane according to claim 1 or 2, characterized in that: The solvent of the high equivalent weight perfluorosulfonic acid resin dispersion includes one or more of dimethyl sulfone, N,N-dimethylformamide, and propylene glycol methyl ether acetate.

6. The method for preparing a high-durability liquid flow battery separator according to claim 1 or 2, characterized in that: The thermosetting curing agent includes one or more of triethylamine, triethanolamine, and tris(dimethylaminomethyl)phenol; the addition amount of the thermosetting curing agent is 0.05-0.5wt%.

7. A method for preparing a high-durability flow battery diaphragm, characterized in that: The following steps are included: Step 1: adding a thermosetting epoxysulfonic acid resin and a thermosetting curing agent to a high equivalent weight perfluorosulfonic acid resin dispersion having a resin equivalent weight of 900 to 1300 g / mol to obtain a dispersion 1, applying a film by scraping, laying a layer of ePTFE reinforcement layer, and heating at 50 to 60° C. to obtain a film 1; Step 2: coating a low equivalent weight perfluorosulfonic acid resin dispersion on the ePTFE reinforcement layer of the film 1 and adding the ePTFE reinforcement layer, and heating at 50-60° C. to obtain an intermediate layer; wherein the resin equivalent of the low equivalent weight perfluorosulfonic acid resin is 760-850 g / mol; Step 3: coating the dispersion 1 on the membrane obtained in step 2, and curing and molding the membrane to obtain the high-durability liquid flow battery separator.

8. The method for preparing a high-durability liquid flow battery separator according to claim 7, characterized in that: In step 2, the amount of perfluorosulfonic acid resin added to the low equivalent weight perfluorosulfonic acid resin dispersion is 10-30wt%; the intermediate layer is provided with several layers, and in the intermediate layer, the low equivalent weight perfluorosulfonic acid resin layer and the ePTFE reinforcement layer are provided at intervals.

9. The method for preparing a high-durability liquid flow battery separator according to claim 7, characterized in that: 0.1-1 wt% of cerium nitrate and 0.1-1 wt% of Triton X-100 are also added to the low-equivalent perfluorosulfonic acid resin dispersion. 10 . The liquid flow battery separator prepared by the method for preparing a high-durability liquid flow battery separator according to claim 1 .